Contextual Effect of Integrated Heath Post on Nutritional Status among Children Aged 6-59 Months in Surabaya, East Java - Aziza, Triana Ulfa Nur; Dewi, Yulia Lanti Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: A child will come into toddler phase which is the rapid growth and development phase. It turns children into one of the groups that vulnerable to suffer from undernutrition. The data of Riskesdas (Basic Health Research) in 2018 indicates that the percentage of malnutrition and undernutrition